Pre- and Postlicensure Animal Efficacy Studies Comparing Anthrax Antitoxins. (17th October 2022) - Slay, Raymond M; Cook, Rachel; Hendricks, Katherine; Boucher, David; Merchlinsky, Michael
Abstract: Background: The deliberate use of Bacillus anthracis spores is believed by the US government to be a high bioweapons threat. The first line of defense following potential exposure to B. anthracis spores would be postexposure prophylaxis with antimicrobials that have activity against B. anthracis. Additional therapies to address the effects of toxins may be needed in systemically ill individuals. Over the last 2 decades, the United States government (USG) collaborated with the private sector to develop, test, and stockpile 3 antitoxins: anthrax immunoglobulin intravenous (AIGIV), raxibacumab, and obiltoxaximab. All 3 products target protective antigen, a protein factor common to the 2 exotoxins released by B . anthracis, and hamper or block the toxins' effects and prevent or reduce pathogenesis. These antitoxins were approved for licensure by the United States Food and Drug Administration based on animal efficacy studies compared to placebo. Methods: We describe USG-sponsored pre- and postlicensure studies that compared efficacy of 3 antitoxins in a New Zealand White rabbit model of inhalation anthrax; survival following a lethal aerosolized dose of B . anthracis spores was the key measure of effectiveness. To model therapeutic intervention, intravenous treatments were started following onset of antigenemia. Results: In pre- and postlicensure studies, all 3 antitoxins were superior to placebo; in the postlicensure study, raxibacumab and obiltoxaximab were superior to AIGIV, but neither was superior to the other. Conclusions: These data illustrate the relative therapeutic benefit of the 3 antitoxins and provide a rationale to prioritize their deployment. Abstract : Pre- and postlicensure inhalation anthrax studies compared efficacy of a polyclonal and 2 monoclonal antibodies against protective antigen in New Zealand White rabbits. Each antitoxin administered at antigenemia onset improved outcomes over placebo. Monoclonal antibodies were superior to polyclonal.